ANALYSIS OF THE EFFECT OF ACCESSIBILITY, FACILITIES, AND STAFF COMMUNICATION ON OUTPATIENT PATIENT SATISFACTION AT KOLONODALE REGIONAL HOSPITAL, NORTH MOROWALI, CENTRAL SULAWESI - Muhammad Anwar; Vip Paramarta; Kosasih; Farida Yuliaty; Fitriana; Taufan Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Patient satisfaction is the main goal of health services. Patient satisfaction is due to the quality of complete services. Several factors identified that influence patient satisfaction include: accessibility, facilities, and staff communication. This study aims to analyze the effect of accessibility, facilities, and staff communication on outpatient satisfaction at Kolonodale Regional Hospital, North Morowali, Central Sulawesi. This research method is a quantitative approach. The number of samples is 100 patients. The sampling technique uses an accidental sampling method. Data were obtained by filling out a questionnaire using a Likert scale and then analyzed using multiple linear regression with SPSS application. The results of the study show the effect of accessibility on patient satisfaction with a value (0.016 < 0.05), then the effect of facilities on patient satisfaction with a value (0.00 < 0.05), then the effect of staff communication on patient satisfaction with a value (0.00 < 0.05), and the effect of accessibility, facilities, and staff communication simultaneously on patient satisfaction is positive and significant (0.000 < 0.05). The magnitude of the coefficient of determination (r2 square) = 0.536; This means that the variables of accessibility, facilities, and staff communication collectively influence patient satisfaction by 53.6%, with the remaining 46.4% influenced by other variables. Therefore, the influence of accessibility, facilities, and staff communication, both partially and simultaneously, on patient satisfaction is positive and significant.